SP4.2.2 Recovery after Emergency Laparotomy – what do patients want?. (9th August 2022) - Silva, L; Crole Rees, C; Watts, T; Bisson, J; Cornish, JA
Abstract: Aim: Recent focus on Emergency Laparotomy outcomes has improved mortality, but little attention has been given to recovery. The aim of this qualitative study was to explore recovery after EmLap. Method: A focus group was established of ten EmLap patients. Inclusion criteria: EmLap<5 years ago, non-palliative. Patients were selected to provide balance of age, sex and pathology. Thematic qualitative analysis was performed by two researchers. Results: Several key themes were highlighted; Lack of communication on diagnosis/expectations after surgery. Little continuity of care. Long delays in seeing doctors after surgery and no way to contact them and GPs unable to help. Financial consequences are significant, with no guidance. Took longer to recover than expected, difficult to explain to employer. Led to early retirement or change of hours/role. Hernias; Some patients aware of hernia risk but given conflicting advice, e.g avoid lifting and rest for 6 weeks, others told to exercise regularly. Difficult to access support garments. Diet – Conflicting advice on what they could/couldn't eat, especially fibre. Felt more by patients who had stoma or bowel resection. Poor quality food in hospital and lack of options for diet (e.g. vegan, coeliac). Poor mental health after surgery with anxiety, depression and loss of confidence all having large impact, especially on relationships and intimacy. Key issues lack of access to services and waiting times. Too 'complex' for primary care. Conclusions: The impact of emergency surgery on patients is significant, particularly mental health and financial impact. Recommend standardised information (leaflets/website/signposting) and key support worker.